O currículo de educação física na ótica das relações étnico-raciais: a prática pedagógica de professores da diretoria regional do Campo Limpo - Lopes, Franz Carlos Oliveira (2020)
The “organized” slavery by some European countries within African lands caused in the most dissimilar spaces of that continent, an atrocity with diverse peoples who lived their lives together with their collectives. In addition, the forced removal of these groups from African soil has caused a lot of physical, psychological, social and cultural damage. In this context, the so-called African diaspora had consequences mainly in countries in America. Brazil, as a colony of those countries that committed the inhumanity of slavery and engaged in the slave trade of blacks, was the country that received the most people for this practice since the mid-16th century. As a justification for the validation of tyranny, the term “race” was used to lower people who did not fit the standards imposed by many Europeans. However, innumerable forms of resistance were coordinated by groups of blacks who live under such conditions of oppression. The organization of these collectives has gone on for a long time and still exists today. With the struggles fought during this period, the claims of descendants of slaves materialized in the country in reparation policies. Law 10.639 / 03 and the curricular guidelines for ethnic-racial relations were expressive results of rights for the education of Afro and Afro-Brazilian culture. However, as much as the inclination towards pedagogy guided by these documents is concentrated in some areas of knowledge, it is important to emphasize that even the components that are outside the indicated mandatory must approach the theme in an investigative way. It is in this sense that the object of this research has, in its orbit, the training of teachers and, at its center, the curricular practices of Physical Education teachers from the Municipal Education Network of the Municipality of São Paulo, whose positions are linked to the Regional Directorate from Campo Limpo. The construction of the hypothesis that guides this work took into account the relevance of institutional documents and turns to training organized by DRE-CL and SME. Thus, the question pursued throughout the research was the following: would these mechanisms be important with current issues to make the pedagogical practice of teachers, especially in Physical Education, materialize? The paths chosen at the heart of qualitative research were two: on the one hand, the construction of “texts” as a means of interpreting various forms of language in the most different contexts, both social, cultural or interpretive, a procedure that produces knowledge weaving interpretations complex about the realities in the social scene; and, on the other, Cultural Studies, which constitute the central theoretical framework for understanding the object that is based on deciphering the intricacies of heterogeneous cultures, almost always seeking their bases in the most diverse territories of the humanities, in the case of this research, the post-structuralism and post-modernism, which, together with post-colonial studies, contribute to significant analyzes in the context of the curriculum, teacher training and pedagogical practice.